Relationship between socio-demographic profile and breastfeeding practice among mothers in Selangor,Malaysia : a cohort Study / Adibah Mohamad Daud…[et al.] - Mohamad Daud, Adibah; Mohamad Kamis, Nooramira; Abdul Ghafar, Nur Sabira; Rafiee Louis, Nurul Rafatin (2014)
The World Health Organization (WHO) recommends exclusive breastfeeding until 6 months of age. The focus of this research is to identify whether socio-demographic factors affect the breastfeeding practice in term of initiation and duration of breastfeeding in a cohort of 146 subjects who age between 18 to 40 years old. This study was done among third trimester pregnant mother selected from the Maternal and Child Health (MCH) section of the government health clinics in Selangor. The Iowa Infant Feeding Attitude Scale (IIFAS) has been used to assess the association of knowledge with the time of initiation and duration of breastfeeding by mothers. This study is a quantitative research followed by questionnaire at third trimester of pregnancy, telephones interviews at first and third after delivery, and home-visit at sixth month after delivery. The expected outcome of this study is socio-demographic factors such as maternal age, residential areas, maternal economic status, maternal education level, parity and maternal employment status strongly affect breastfeeding practice among the target population. Result indicated education background and household income show significant association with the time of initiation of breastfeeding. The most important socio demographic characteristic associated with duration of breastfeeding during three and six months were mother's age and employment status. Besides, infant feeding knowledge of the mothers does not showed any significant association with both the time of breastfeeding initiation and duration. In conclusion, some of the demographic characteristics showed significant association with the time of initiation of breastfeeding and duration of breastfeeding during three and six months. The IIFAS, while predictive of breastfeeding knowledge of the mothers was not associated with both the time of breastfeeding initiation and duration. The findings of this study can be useful for government in adapting and developing policy regarding breastfeeding practice in Malaysia.